ACTITUDES Y CONOCIMIENTO SOBRE SEXUALIDAD DE LA CARRERA DE PSICOPEDAGOGÍA” RIOBAMBA, PERIODO MARZO – AGOSTO 2019 - Padilla Padilla, Jessica Paola (2020)
The purpose of this was to determine attitudes and knowledge about sexuality in students of first, second, third, and fourth-semester of the Psychopedagogy career have about sexuality, Facultad de Ciencias de la Educacion Humanas y Tecnologias from Universidad Nacional de Chimborazo period March-August 2019. Human Sexuality is a multidimensional phenomenon that includes biological, psychosocial, behavioral, clinical, moral and cultural aspects. Therefore, knowledge and attitudes are considered necessary variables for the formation of sexuality. However, it does not mean that they are sufficient for healthy behavior. For this reason, this research project describes the research variables and know about sexuality in young university students. Methodologically, the research used the qualitative approach. The research design in non-experimental since the variables were not manipulated. It is a transversal type research with a descriptive and correlational research level for the fundamental objective and by the place of the field. The population was the students Universidad Nacional de Chimborazo. The sample was no probabilistic because it worked it 125 students, 32 men and 93 women from the first, second third, and fourth semester of the Psychopedagogy career. The instrument used is liker scale surveys for the two variables. It facilitated the analysis and interpretation of the date for a subsequent correlation with the variables studied.